On a Quasi-Neutral Approximation to the Incompressible Euler Equations - Jianwei Yang; Zhitao Zhuang (Journal of Applied Mathematics)
We rigorously justify a singular Euler-Poisson approximation of the incompressible Euler equations in the quasi-neutral regime for plasma physics. Using the modulated energy estimates, the rate convergence of Euler-Poisson systems to the incompressible Euler equations is obtained.